A food crisis was brewing even before the Ukraine war- but taking these three steps could help the most vulnerable - Headey, Derek D.; Hirvonen, Kalle (International Food Policy Research Institute, 2023)
Russia’s invasion of Ukraine has led to the disruption, by sanctions or war, of two of the world’s largest grain exporters. This means 2022 is shaping up to be a very difficult year for the global food system. Yet there were concerns that this system was creaking at the seams as far back as 2007. At that time, there were steeply rising food prices driven by rising oil prices, explosive demand for corn-based biofuels, high shipping costs, financial market speculation, low grain reserves, severe weather disruptions in some major grain produc ers, and a swath of nervy trade policies leading to further shocks that worsened the problem. The World Food Program’s director general described it as a “perfect storm.” Prices spiked again in 2011/12 before gradually receding. In retrospect, those storms might now appear temperate in comparison to that we face in 2022. Even before the current crisis unfolded, food, fertilizer, oil, and shipping costs were rising steeply. The FAO cereal price index shows prices hit their 2008 level in 2021, and since the invasion they have explod ed. Between 2019 and March 2022, cereal prices increased by 48%, fuel prices by 86%, and fertilizer prices by 35% (Figure 1). Here are three factors that we think make the situation in 2022 much worse, and three measures that could help prevent a global food supply system collapse